Pengaruh Kualitas Pelayanan terhadap Kepuasan Pelanggan pada Warunk Gacoan Colombo Sleman Yogyakarta - Abdul Rhosid Saputro; Suparmono Suparmono (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2020)
This study aims to explain the effect of service quality variables on customer satisfaction at Warunk Gacoan Colombo, Yogyakarta. The variables used for service quality consist of: Tangible, Reliability, Responsiveness, Assurance, Empathy. The sampling method used purposive sampling technique, namely sampling based on considerations in accordance with the purpose of the study, with a sample size of 130 respondents obtained by the Hair formula. The data analysis techniques used were instrument test, basic assumption test, classical assumption test, multiple linear regression analysis, and hypothesis testing. Based on the analysis results that have been described, it can be concluded that the variables reliability, tangible, assurance, and empathy have a positive and significant effect on customer satisfaction. Responsiveness has a negative and insignificant effect on customer satisfaction. Meanwhile, the variables have a positive and insignificant effect on customer satisfaction. The contribution of this study is in terms of the finding that the quality of service in the restaurant business which is developing and becoming a trend for young people is that responsiveness is not so considered in determining service satisfaction.